2022
DOI: 10.46519/ij3dptdi.1069544
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on the Effect of Test Speed on the Tensile Properties of the Petg Produced by Additive Manufacturing

Abstract: Additive manufacturing (AM) is a highly popular, versatile, and practical production technique due to its great ability of very fast prototyping. Compared to other traditional ways, the number of studies on AM techniques has increased in a noteworthy manner day by day on account of their promising potential for future works. In this paper, fused deposition modeling (FDM) technology was used to fabricate polyethylene terephthalate glycol (PETG) specimens and to analyze the effect of the test speed on their tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The plastic materials’ mechanical properties have a strong relation with the testing speed. For this purpose, Ergene and Bolat 24 concluded that the lower testing speeds resulted in higher plastic behavior and in contrast, higher testing speed resulted in the brittle failure mechanism. It is worth noting that one of the important manufacturing parameters is the infill density and it was proved that the higher infill density resulted in higher impact properties.…”
Section: Introductionmentioning
confidence: 99%
“…The plastic materials’ mechanical properties have a strong relation with the testing speed. For this purpose, Ergene and Bolat 24 concluded that the lower testing speeds resulted in higher plastic behavior and in contrast, higher testing speed resulted in the brittle failure mechanism. It is worth noting that one of the important manufacturing parameters is the infill density and it was proved that the higher infill density resulted in higher impact properties.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (8) and (9) ShownThe PETG/Carbon samples had a hardness (Shore D) that was 2.16% lower than PETG's At produced FDM technology in the 3D printed where the average of hardness (Shore-D) equaled 73.74 D, 72.14D respectively at added 15% carbon fiber filler and Micro-hardness test was slightly increased of HV hardness of PETG/Carbon samples, where it equaled 10.4 HV but for PETG equaled 9.6 HV. These features were stated to improve the sliding properties of carbon fiber in PETG/Carbon samples, but at the buried structure of samples, the carbon fiber was made a stronger bond with a matrix of PETG polymers and good compatibility with it; suggested that an effective manufacturing technology to generate homogenized composite materials is a 3D printer and this can explicated by the number of stacked layers for PETG/Carbon[15],[14].…”
mentioning
confidence: 99%